Valid publication of Turpinia pomifera var. minor (Staphyleaceae) - Yu, Wen-Bin (Phytotaxa, 2013)
Turpinia Ventenat (1807: 3, non. cons.) is the largest genus of Staphyleaceae (Li et al. 2008). About 13 species are recorded from China, five of which are endemic. Turpinia pomifera var. minor C.C.Huang ex Hsu (1979: 358; see comments in Bartholomew & Zhou 2007) was firstly described in Flora Yunnanica. However, it was not validly published, because no specimen was listed in the protologue, which is contrary to Article 40.1 & 40.2 (McNeill et al. 2012). After consulting the herbarium of Kunming Institute of Botany (KUN), Chinese Academy of Sciences, we found that three gatherings (K.M.Feng 11588, 11748, 13544) were annotated as “Turpinia pomifera (Rox.) Kong [corrected as DC.] var. minor Huang var. n.” [sic] by C.C.Huang in April 1960 on the sheets. Therefore, the three gatherings will potentially have been examined by C.C. Huang and may have been used for the description of T. pomifera var. minor in the preparation of Flora Yunnanica. To validate the name of this variety, a sheet of the gathering K.M.Feng 11588 is designated as the holotype (Fig. 1). Ting-Zhi Hsu published a Latin diagnosis of this variety in 1979, which is referred to below to satisfy Article 39.1. According to Article 46.2, the authorship of the name T. pomifera var. minor remains the same